Pengaruh Budaya Organisasi dan Motivasi Kerja terhadap Kinerja Petugas Aviation Security di Bandar Udara Mutiara SIS Al-Jufri Palu - Frisnawati, Elnia; Gerosi, Michael Prayoga (Sekolah Tinggi Teknologi Kedirgantaraan, 2024)
This study aims to determine (1) whether organizational culture influences the performance of AVSEC officers at Mutiara Sis Al-Jufri Airport, Palu, (2) whether work motivation influences the performance of AVSEC officers at Mutiara Sis Al-Jufri Airport, Palu, and (3) whether organizational culture and work motivation simultaneously influence the performance of AVSEC officers at Mutiara Sis Al-Jufri Airport, Palu. This study was conducted from May 1 to June 30, 2024 at Mutiara Sis Al-Jufri Airport, Palu. This study uses a quantitative method with a type of survey conducted on AVSEC officers and passengers using a questionnaire distribution. In this study, questionnaires were distributed to 97 AVSEC officers and 97 passengers. The data analysis techniques used were normality test, heteroscedasticity test, multicollinearity test, multiple linear regression analysis, hypothesis test, and determination coefficient test (R²). The results of the study show that: (1) organizational culture has a positive influence on the performance of AVSEC officers at Mutiara Sis Al-Jufri Airport, Palu, (2) work motivation has a positive influence on the performance of AVSEC officers at Mutiara Sis Al-Jufri Airport, Palu, and (3) organizational culture and work motivation simultaneously have a positive influence on the performance of AVSEC officers at Mutiara Sis Al-Jufri Airport, Palu.